Pengaruh Mata Kuliah Kewirausahaan dan Media Sosial terhadap Minat Berwirausaha di Kalangan Mahasiswa - Adi Masliardi; Doni Mardiyanto; Mochamad Sarif Hasyim; Cut Nuraini; July Yuliawati; Abdullah Zailani (JURNAL ILMIAH EDUNOMIKA, 2025)
AbstractThis study aims to examine the influence of entrepreneurship courses and the use of social media on students' entrepreneurial interest in Karawang Regency. Using quantitative methods with multiple regression analysis, this study involved 150 students from Singaperbangsa University, Karawang, and Buana Perjuangan University, Karawang. The results showed that (1) entrepreneurship courses had a positive and significant effect on entrepreneurial interest (t = 2.737, p = 0.008); (2) the use of social media also had a positive and significant effect on entrepreneurial interest (t = 5.512, p = 0.000); and (3) together, these two factors contributed 55.5% to students' entrepreneurial interest (F = 36.162, p = 0.000). These findings indicate the importance of universities optimizing their entrepreneurship curriculum and utilizing social media in the learning process to increase students' entrepreneurial interest. Keywords: entrepreneurship, social media, entrepreneurial interest, students, higher education